Kajian Uji Campuran Mortar K-50 dengan Komposisi Campuran untuk Perkerasan Ruas Jalan di Dinas PUPR Kabupaten Timor Tengah Selatan - Maria Cresentia Watihena; Dian Noorvy Khaerudin; Paulus Cindrawan Telnoni (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Mortar mixture is one of the important binding elements in civil works, with a minimum standard compressive strength of 50 kg/cm² to achieve a concrete age of 28 days. Mortar with a minimum compressive strength standard of 50 kg/cm², or commonly referred to as Mortar K-50, is used to support the strength of the structure until the concrete age of 28 days. Mortar mixtures are widely used in various types of work with different levels of strength according to their needs. The quality of the mortar is greatly influenced by the composition of the constituent materials, such as the ratio of cement and sand, as well as the soaking time that plays a role in the cement hydration process. This hydration process is important because it determines the homogeneity of the mixture and the final strength of the resulting mortar. This study aims to determine the compressive strength value of mortar with variations in the composition of the cement and sand mixture, namely a ratio of 1:3, 1:4, and 1:5, as well as the effect of curing time at the age of 7, 14, and 28 days. Testing was carried out using a cube-shaped mortar test specimen measuring 5 x 5 x 5 cm. The sand used comes from the Ex AlkaniRiver, with grain sizes ranging from 0.075 mm to 4.80 mm and a fineness modulus of 2.5 to 3.2. The cement used was Kupang Type I Cement, a standard Portland cement that meets SNI standards. The test specimens were cured under laboratory conditions to ensure optimal hydration. The results of the study showed that the compressive strength of mortar with a mixture of 1:3 produced a higher strength of 76.65 MPa above the minimum mortar compressive strength of 50 MPa. Mixtures with a ratio of 1:4 and 1:5 showed compressive strengths of 54.66 MPa and 44.7 MPa.